Line 6: Line 6:
  
 
<center>
 
<center>
==Inverse Z Transform *under construction*==
+
==Inverse Z Transform *under construction last updated 4:11 am 12/20/14*==
 
</center>
 
</center>
  
  
 
'''Introduction'''
 
'''Introduction'''
 
+
The Z Transform is the generalized version of the DTFT. You can obtain the Z Transform from the DTFT by replacing <math>e^{j\omega}</math> with <math> re^{j\omega} </math> which is equivalent to z. The The DTFT is equal to the Z Transform when <math>|z| =1 </math>  
The Z Transform is the generalized version of the DTFT. You can obtain the Z Transform from the DTFT by replacing <math>e^{j\omega}</math> with <math> re^{j\omega} = z </math>. The The DTFT is equal to the Z Transform when <math>|z| =1 </math>  
+
  
 
<math>
 
<math>
Line 32: Line 31:
  
 
'''Region of Convergence (ROC)'''
 
'''Region of Convergence (ROC)'''
 
 
The ROC determines the region on the Z Plane where the Z Transform converges. The ROC depends solely on the 'r' value that is contained in 'z'. The ROC is always one of three cases;
 
The ROC determines the region on the Z Plane where the Z Transform converges. The ROC depends solely on the 'r' value that is contained in 'z'. The ROC is always one of three cases;
 
:1. The ROC starts from a circle centered at the origin and extends outward to infinity
 
:1. The ROC starts from a circle centered at the origin and extends outward to infinity
 
:2. The ROC starts from a circle centered at the origin and fills in toward the origin
 
:2. The ROC starts from a circle centered at the origin and fills in toward the origin
 
:3. The ROC is the space in-between two circles centered at the origin.
 
:3. The ROC is the space in-between two circles centered at the origin.
If the ROC includes the unit circle then the DTFT exists for that function if it is not included, then it does not exist.
+
If the ROC includes the unit circle then the DTFT converges for that function if it is not included, then it does not.
  
 
<math>
 
<math>
Line 46: Line 44:
 
</math>
 
</math>
  
""II. Example Problems of the Inverse Z Transform""
+
The ROC is determined when preforming Z transforms and is given when preforming inverse Z transforms.
  
 +
'''Solving an inverse Z Transform'''
 +
To find the Inverse Z transform of signals use manipulation then direct Inversion. Do not use formula directly!
  
:We will find the Inverse Z transform of various signals by manipulation and then using direct Inversion.
+
The Infinite Geometric Series formula is used in most problems involving Inv. Z transform.
:On the first example we will go slowly over each step.
+
  
Ex. 1 Find the Inverse Z transform of the following signal
+
<math>
 +
\begin{align}
 +
\text{Infinite Geometric Series: }
 +
X(z) &= \frac{a}{1-r}\\
 +
      &= \sum_{n=0}^{\infty} (a)r^{n} , \text{if } |z| < 1\\
 +
      &= \sum_{n=-\infty}^{\infty} (a)r^{n} u[n]\\
 +
\end{align}
 +
</math>
  
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|<1 </math>
+
it can be seen that this general form is already starting to look like that of the Z Transform, with some change of variables we can manipulate this equation to be that of a Z transform and then by comparison find the inverse z transform.
  
::note: It is important to realize that we are not going to try to use the direct formula for an inverse Z transform, Instead our approach will be to manipulate the signal so that we can directly compare it with the Z transform equation and by inspection obtain the Inverse Z transform.
+
'''Examples'''
  
:First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z
+
Ex. 1 Find the Inverse Z transform of the following signal
<center><math>|A| < 1</math></center>
+
  
:In this case this is already satisfied with
+
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|<1 </math>
<center><math>A = z</math></center>
+
  
:Then we need to manipulate the given signal to be in the following form, B is just some expression that is the result of adjusting the equation (in this case B = 1)
+
Solution
<center><math>X(z)=B\frac{1}{1-A}</math></center>
+
  
:Using a infinite Geometric sum we can obtain following...
+
<math>
 
+
\begin{align}
<center><math>X(z) = \sum_{n=0}^{\infty} 1(z^{n}) = \sum_{n=-\infty}^{\infty} z^{n} u[n]</math></center>
+
X(x) &= \frac{1}{1-z}\\
 
+
      &= \sum_{n=0}^{\infty} 1(z^{n}) \text{  if } |z| < 1\\
<center><math>\text{let } k = -n \text{ then, } X(z) = \sum_{k=-\infty}^{\infty} z^{-k} u[-k]= \sum_{k=-\infty}^{\infty}u[-k] z^{-k}</math></center>
+
      &= \sum_{n=-\infty}^{\infty} z^{n} u[n]\\
 
+
      &\text{let }k = -n\\
: By comparison with the Z Transform definition, we can determine <math> x[n] </math>
+
      &= \sum_{k=-\infty}^{\infty} z^{-k} u[-k]\\
 
+
      &= \sum_{k=-\infty}^{\infty}u[-k] z^{-k}\\
<center><math>x[n] = u[-n]</math></center>
+
      &\text{By comparison with the Z Transform definition..}\\
 +
x[n] &= u[-n]\\
 +
\end{align}
 +
</math>
  
 
Ex. 2 Find the Inverse Z transform of the following signal  
 
Ex. 2 Find the Inverse Z transform of the following signal  
Line 81: Line 87:
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|>1 </math>
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|>1 </math>
  
:First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z
+
Solution
<center><math>|A| < 1</math></center>
+
  
:In this case
+
<math>
<center><math>A = \frac{1}{z}</math></center>
+
\begin{align}
 
+
X(z) &= \frac{1}{1-z} \\
:Manipulate the given signal
+
      &= \frac{1}{z} \frac{1}{1-(-\frac{1}{z})}\\
<center><math>X(z)=\frac{1}{1-z} = \frac{1}{z} \frac{1}{1-(-\frac{1}{z})}</math></center>
+
      & \text{Using a infinite Geometric series...}\\
 
+
      &= \sum_{n=0}^{\infty} (\frac{-1}{z})^{n}\frac{1}{z} \text{  if } |-\frac{1}{z}| < 1\\
:Using a infinite Geometric sum we can obtain
+
      &=  \sum_{n=0}^{\infty}(-1)^{n} z^{-n-1} \\
 
+
      &=  \sum_{n=-\infty}^{\infty} (-1)^{n} z^{-n-1} u[n]\\
<center><math>X(z) = \sum_{n=0}^{\infty} (\frac{-1}{z})^{n}\frac{1}{z} =  \sum_{n=0}^{\infty}(-1)^{n} z^{-n-1} =  \sum_{n=-\infty}^{\infty} (-1)^{n} z^{-n-1} u[n]</math></center>
+
      &\text{ let } k=n+1 \\
 
+
      &=  \sum_{k=-\infty}^{\infty}(-1)^{k-1} z^{-k} u[k-1] \\
<center><math> \text{ let } k=n+1, \text{ then } X(z) =  \sum_{k=-\infty}^{\infty}(-1)^{k-1} z^{-k} u[k-1] =  \sum_{k=-\infty}^{\infty} (-1)^{k-1} u[k-1] z^{-k}</math></center>
+
      &=  \sum_{k=-\infty}^{\infty} (-1)^{k-1} u[k-1] z^{-k}\\
 
+
      &\text{By comparison with the Z Transform definition...}\\
:By comparison with the Z Transform definition, we can determine <math> x[n] </math>
+
x[n] &=(-1)^{n-1} u[n-1]\\
 +
\end{align}
 +
</math>
  
<center><math>x[n] = (-1)^{n-1} u[n-1]</math></center>
 
  
 
Ex. 4 Find the Inverse Z transform of the following signal  
 
Ex. 4 Find the Inverse Z transform of the following signal  
Line 104: Line 110:
 
<math>X(z)=\frac{1}{1-2z}, \text{ ROC } |2z|>1 </math>
 
<math>X(z)=\frac{1}{1-2z}, \text{ ROC } |2z|>1 </math>
  
:Manipulate the given signal
+
Solution
  
<center><math>X(z)=\frac{1}{1-2z} = \frac{1}{2z} \frac{1}{1-(-\frac{1}{2z})}</math></center>
+
<math>
 
+
\begin{align}
:Using a infinite Geometric sum we can obtain
+
X(z) &= \frac{1}{1-2z}\\
 
+
      &= \frac{1}{2z} \frac{1}{1-(-\frac{1}{2z})}\\
<center><math>X(z) = \sum_{n=0}^{\infty} (\frac{-1}{2z})^{n}\frac{1}{2z} = \sum_{n=0}^{\infty} (-2z)^{-n}(2z)^{-1}= \sum_{n=-\infty}^{\infty} \frac{1}{2}(-2)^{-n}z^{-n-1} u[n]</math></center>
+
      &= \sum_{n=0}^{\infty} (\frac{-1}{2z})^{n}\frac{1}{2z} \text{  if } |-\frac{1}{2z}| < 1\\
 
+
      &= \sum_{n=0}^{\infty} (-2z)^{-n}(2z)^{-1}\\
<center><math> \text{ let } k=n+1, \text{ then } X(z) = \sum_{k=-\infty}^{\infty} \frac{1}{2}(-2)^{-k+1}u[k-1] z^{-k}</math></center>
+
      &= \sum_{n=-\infty}^{\infty} \frac{1}{2}(-2)^{-n}z^{-n-1} u[n]\\
 
+
      &\text{ let } k=n+1\\
: By comparison with the Z Transform definition, we can determine <math> x[n] </math>
+
      &= \sum_{k=-\infty}^{\infty} \frac{1}{2}(-2)^{-k+1}u[k-1] z^{-k}\\
 
+
      &\text{By comparison with the Z Transform definition...}\\
<center><math>x[n] = \frac{1}{2}(-2)^{-k+1}u[n-1]</math></center>
+
x[n] &= \frac{1}{2}(-2)^{-k+1}u[n-1]\\
 +
\end{align}
 +
</math>

Revision as of 23:50, 19 December 2014


Inverse Z Transform *under construction last updated 4:11 am 12/20/14*


Introduction The Z Transform is the generalized version of the DTFT. You can obtain the Z Transform from the DTFT by replacing $ e^{j\omega} $ with $ re^{j\omega} $ which is equivalent to z. The The DTFT is equal to the Z Transform when $ |z| =1 $

$ \begin{align} \text{DTFT: } X(w) &= \sum_{n=-\infty}^\infty x[n]e^{-j\omega n}\\ \text{Z-Transform: } X(z) &= \sum_{n=-\infty}^\infty x[n]z^{-n}\\ \text{Inv. Z-Transform: } x[n] &= \frac{1}{2\pi j}\oint_{c}X(z)z^{n-1}dz \end{align} $

Region of Convergence (ROC) The ROC determines the region on the Z Plane where the Z Transform converges. The ROC depends solely on the 'r' value that is contained in 'z'. The ROC is always one of three cases;

1. The ROC starts from a circle centered at the origin and extends outward to infinity
2. The ROC starts from a circle centered at the origin and fills in toward the origin
3. The ROC is the space in-between two circles centered at the origin.

If the ROC includes the unit circle then the DTFT converges for that function if it is not included, then it does not.

$ \begin{align} \text{Remember: } z &=re^{j\omega} \end{align} $

The ROC is determined when preforming Z transforms and is given when preforming inverse Z transforms.

Solving an inverse Z Transform To find the Inverse Z transform of signals use manipulation then direct Inversion. Do not use formula directly!

The Infinite Geometric Series formula is used in most problems involving Inv. Z transform.

$ \begin{align} \text{Infinite Geometric Series: } X(z) &= \frac{a}{1-r}\\ &= \sum_{n=0}^{\infty} (a)r^{n} , \text{if } |z| < 1\\ &= \sum_{n=-\infty}^{\infty} (a)r^{n} u[n]\\ \end{align} $

it can be seen that this general form is already starting to look like that of the Z Transform, with some change of variables we can manipulate this equation to be that of a Z transform and then by comparison find the inverse z transform.

Examples

Ex. 1 Find the Inverse Z transform of the following signal

$ X(z)=\frac{1}{1-z}, \text{ ROC } |z|<1 $

Solution

$ \begin{align} X(x) &= \frac{1}{1-z}\\ &= \sum_{n=0}^{\infty} 1(z^{n}) \text{ if } |z| < 1\\ &= \sum_{n=-\infty}^{\infty} z^{n} u[n]\\ &\text{let }k = -n\\ &= \sum_{k=-\infty}^{\infty} z^{-k} u[-k]\\ &= \sum_{k=-\infty}^{\infty}u[-k] z^{-k}\\ &\text{By comparison with the Z Transform definition..}\\ x[n] &= u[-n]\\ \end{align} $

Ex. 2 Find the Inverse Z transform of the following signal

$ X(z)=\frac{1}{1-z}, \text{ ROC } |z|>1 $

Solution

$ \begin{align} X(z) &= \frac{1}{1-z} \\ &= \frac{1}{z} \frac{1}{1-(-\frac{1}{z})}\\ & \text{Using a infinite Geometric series...}\\ &= \sum_{n=0}^{\infty} (\frac{-1}{z})^{n}\frac{1}{z} \text{ if } |-\frac{1}{z}| < 1\\ &= \sum_{n=0}^{\infty}(-1)^{n} z^{-n-1} \\ &= \sum_{n=-\infty}^{\infty} (-1)^{n} z^{-n-1} u[n]\\ &\text{ let } k=n+1 \\ &= \sum_{k=-\infty}^{\infty}(-1)^{k-1} z^{-k} u[k-1] \\ &= \sum_{k=-\infty}^{\infty} (-1)^{k-1} u[k-1] z^{-k}\\ &\text{By comparison with the Z Transform definition...}\\ x[n] &=(-1)^{n-1} u[n-1]\\ \end{align} $


Ex. 4 Find the Inverse Z transform of the following signal

$ X(z)=\frac{1}{1-2z}, \text{ ROC } |2z|>1 $

Solution

$ \begin{align} X(z) &= \frac{1}{1-2z}\\ &= \frac{1}{2z} \frac{1}{1-(-\frac{1}{2z})}\\ &= \sum_{n=0}^{\infty} (\frac{-1}{2z})^{n}\frac{1}{2z} \text{ if } |-\frac{1}{2z}| < 1\\ &= \sum_{n=0}^{\infty} (-2z)^{-n}(2z)^{-1}\\ &= \sum_{n=-\infty}^{\infty} \frac{1}{2}(-2)^{-n}z^{-n-1} u[n]\\ &\text{ let } k=n+1\\ &= \sum_{k=-\infty}^{\infty} \frac{1}{2}(-2)^{-k+1}u[k-1] z^{-k}\\ &\text{By comparison with the Z Transform definition...}\\ x[n] &= \frac{1}{2}(-2)^{-k+1}u[n-1]\\ \end{align} $

Alumni Liaison

Correspondence Chess Grandmaster and Purdue Alumni

Prof. Dan Fleetwood